2016
DOI: 10.1002/joc.4759
|View full text |Cite
|
Sign up to set email alerts
|

A new classification algorithm for daughter cyclone formation with respect to the parent's frontal system – application for the Mediterranean Basin

Abstract: This article presents a semi-objective methodology to classify formation scenarios of a new 'daughter' cyclone (DC), based on the thermal field characteristics of the parent cyclone (PC). An automated algorithm assigns a DC to one of seven formation types, according to the following considerations: Whether the DC is formed on a front belonging to the parent's frontal system or to a different frontal system, and whether this frontal system is cold, warm or quasi-stationary. An additional type contains DCs forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…within their warm sector or at the warm front of the parents. Further analysis by Saaroni et al (2017) showed that over half of "daughters" formed on the frontal system of the "parent", one third on a separate frontal system and about 10 % within the warm sector of the "parent" cyclone.…”
Section: Secondary ("Daughter") Cyclonesmentioning
confidence: 99%
“…within their warm sector or at the warm front of the parents. Further analysis by Saaroni et al (2017) showed that over half of "daughters" formed on the frontal system of the "parent", one third on a separate frontal system and about 10 % within the warm sector of the "parent" cyclone.…”
Section: Secondary ("Daughter") Cyclonesmentioning
confidence: 99%
“…Alternatively, some western Mediterranean cyclones are directly impacted by their North Atlantic counterparts via clustering. In this case, a secondary smaller low is formed near an existing storm (Ziv et al, 2015;Saaroni et al, 2017;Priestley et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, MCs have often been referred to as daughter cyclones (Romem et al, 2007;Ziv et al, 2015). Mediterranean daughter cyclones can appear in various regions relative to their parent cyclone, commonly along the parental frontal system but also in the warm sector, or can be linked to a separate synoptic system (Saaroni et al, 2017). Nevertheless, MCs differ strongly by season, location, duration, extent, and impact.…”
Section: Introductionmentioning
confidence: 99%